POLA KOORDINASI ANTARA DINAS SOSIAL DAN SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN ANAK JALANAN YANG MENGGANGGU KETENTRAMAN DAN KETERTIBAN DI KABUPATEN OGAN KOMERING ULU - Jumratussani; Marratu Fahri; Eva Susanti (Jurnal Riset Multidisiplin Edukasi, 2026)
The issue of street children remains a social problem that has not been optimally addressed in Ogan Komering Ulu Regency (OKU). The handling carried out so far tends to be short-term in nature and has not addressed the root causes of the problem. This study aims to analyze the coordination pattern between the Social Service Office and the Civil Service Police Unit (Satpol PP) in controlling street children who disturb public peace and order in Ogan Komering Ulu Regency. This research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The study was conducted from June 1 to June 26, 2025, at the Social Service Office and the Satpol PP of Ogan Komering Ulu Regency. Data analysis was based on Hasibuan’s coordination theory, using the indicators of unity of action, communication, division of labor, and discipline. The results indicate that the coordination pattern between the Social Service Office and Satpol PP has been implemented effectively. Unity of action was achieved through briefings, joint roll calls, and pre-operation meetings, although it has not yet been supported by a formally established joint Standard Operating Procedure (SOP). Communication was conducted in a two-way manner, both formally and informally, enabling quick responses to public reports. The division of labor between agencies was clearly defined according to their respective functions and authorities, preventing overlapping tasks. Discipline was reinforced through internal supervision and leadership role models. The coordination pattern formed is categorized as a functional coordination pattern and is considered effective in addressing street children issues. It is recommended that the local government establish a formal joint SOP and strengthen cross-sectoral coordination to ensure sustainable and rehabilitation-oriented handling of street children.